Differential Intraoperative Effect of Liver Transplant in Different Inborn Errors of Metabolism. Issue 2 (August 2019) - Porta, Francesco; Romagnoli, Renato; Busso, Marta; Tandoi, Francesco; Spada, Marco
Abstract : ABSTRACT: Liver transplant (LT) is a therapeutic option for a growing number of inborn errors of metabolism (IEM), including some disorders not confined to the liver. Clinical advantages of LT in maple syrup urine disease (MSUD), methylmalonic acidemia (MMA), and argininosuccinic aciduria (ASA) have been reported. However, no information on the early metabolic effect of LT after portal reperfusion is available in these disorders. Here we describe the intraoperative differential metabolic outcome of LT in MSUD, MMA, and ASA. In these IEM, LT promptly cleared toxic metabolites to safe concentrations. In MSUD, leucine concentration reached physiological concentration within 12 hours after portal reperfusion. In MMA and ASA, LT allowed faster clearance of methylmalonate and argininosuccinate, respectively, both dropping by ∼90% within the first hour after portal reperfusion. The early biochemical benefits of LT in MSUD, MMA, and ASA demonstrate its immediate effectiveness in protecting patients from intercurrent metabolic decompensations.